The right to life as a personal non-proprietary right of an individual - Слома, Валентина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article examines the right to life as the main non-property right of an individual. The author analyzesthe different scientific views on the subject, and the position of national and international legal act.